2006
DOI: 10.1073/pnas.0608549103
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the uncultivated marine crenarchaeote Cenarchaeum symbiosum

Abstract: Crenarchaeota are ubiquitous and abundant microbial constituents of soils, sediments, lakes, and ocean waters. To further describe the cosmopolitan nonthermophilic Crenarchaeota, we analyzed the genome sequence of one representative, the uncultivated sponge symbiont Cenarchaeum symbiosum. C. symbiosum genotypes coinhabiting the same host partitioned into two dominant populations, corresponding to previously described a-and b-type ribosomal RNA variants. Although they were syntenic, overlapping a-and b-type rib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
372
1
8

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 423 publications
(396 citation statements)
references
References 55 publications
15
372
1
8
Order By: Relevance
“…In order to identify the amino acid residues involved in catalysis and/or substrate recognition, we searched for highly conserved residues by aligning the amino acid sequences of 27 PoK protein homologs from diverse archaeal species. We found that the PoK homologs are present in the recently sequenced genomes of Thaumarchaeota Cenarchaeum symbiosum (8) and Nitrosopumilus maritimus (31). The alignment with nine representative sequences is shown in Fig.…”
Section: Production and Purification Of Recombinant Pantoate Kinasementioning
confidence: 96%
“…In order to identify the amino acid residues involved in catalysis and/or substrate recognition, we searched for highly conserved residues by aligning the amino acid sequences of 27 PoK protein homologs from diverse archaeal species. We found that the PoK homologs are present in the recently sequenced genomes of Thaumarchaeota Cenarchaeum symbiosum (8) and Nitrosopumilus maritimus (31). The alignment with nine representative sequences is shown in Fig.…”
Section: Production and Purification Of Recombinant Pantoate Kinasementioning
confidence: 96%
“…Owing to the nature of the samples and the algorithms used, assembly can produce chimeric contigs and scaffolds comprising reads from different organisms. Strain heterogeneity can add considerably to this problem as the probability of co-assembly increases with closely related genomes 4 .…”
mentioning
confidence: 99%
“…Both come from shallow waters, the sponge symbiont Cenarchaeum symbiosum (Hallam et al, 2006) and the aquarium isolate N. maritimus (Walker et al, 2010). Recently, draft genome sequence has been obtained from single cells and San Francisco Bay sediment enrichments of Nitrosoarchaeum limnia, recovered from an estuary in San Francisco bay (Blainey et al, 2011) and from a soil isolate, Nitrososphaera viennensis (Tourna et al, 2011).…”
Section: Introductionmentioning
confidence: 99%